1996
DOI: 10.1002/(sici)1099-1166(199607)11:7<635::aid-gps363>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Survey of physician practices for community-dwelling agitated dementia patients

Abstract: In order to gain a better understanding of physician clinical reasoning and clinical practices for community‐dwelling agitated dementia patients, we conducted a small survey of geriatric psychiatrists, primary care physicians and neurologists. The survey asked physician respondents to give a likelihood estimate of how often they would carry out one of 13 different pharmacologic and psychosocial interventions. Intervention by specialty group analyses found that geriatric psychiatrists were more likely to recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Three of the descriptive cross‐sectional studies were rated as low quality (achieving only 3 out of 7 quality markers). These studies all reported on the same cohort . The overall quality of the other 4 descriptive cross‐sectional studies ranged from moderate to high (File S6 and Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three of the descriptive cross‐sectional studies were rated as low quality (achieving only 3 out of 7 quality markers). These studies all reported on the same cohort . The overall quality of the other 4 descriptive cross‐sectional studies ranged from moderate to high (File S6 and Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The overall quality of the other 4 descriptive cross‐sectional studies ranged from moderate to high (File S6 and Table ). Common areas of weakness were the lack of involvement of the target population in the instrument development and the lack of clarity on whether the sample used in the study was likely to be representative of the study population . None of the descriptive cross‐sectional studies provided a sample size justification, statistical power description, or variance and effect estimates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a USA survey (Colenda et al, 1996b) comparing physicians' treatment recommendations for agitation in dementia patients, medication use was endorsed over twice as often as nonpharmacological interventions. Recommendations for treatment were found to be affected by physicians' personal characteristics, including age, gender, and specialty (Colenda et al, 1996a), as well as by factors such as being pressured and lacking other options (Cornegé-Blokland et al, 2012). Recommendations for treatment were found to be affected by physicians' personal characteristics, including age, gender, and specialty (Colenda et al, 1996a), as well as by factors such as being pressured and lacking other options (Cornegé-Blokland et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that (1) most physicians will report treating agitation with psychotropic medication, that (2) physicians' treatment modalities will differ by personal characteristics (Colenda et al, 1996a), and that (3) physicians' levels of familiarity with non-pharmacological interventions will differ by personal characteristics. It aims to clarify physicians' actual practice in treating agitation, and to elucidate the relationship between practice, physicians' background factors, and familiarity with interventions.…”
Section: Introductionmentioning
confidence: 99%